ER stress promotes antitumor effects in BRAFi/MEKi resistant human melanoma induced by natural compound 4-nerolidylcathecol (4-NC). (March 2019) - Alves-Fernandes, Débora Kristina; Oliveira, Érica Aparecida de; Faião-Flores, Fernanda; Alicea-Rebecca, Gretchen; Weeraratna, Ashani T.; Smalley, Keiran S.M.; Barros, Silvia Berlanga de Moraes; Maria-Engler, Silvya Stuchi
Graphical abstract: Abstract: Melanoma accounts for only 4% of malignant neoplasms of the skin, but is considered the most serious because it is highly deadly. Mutations in the MAPK (Ras-Raf-MEK-ERK) pathway is closely linked to the lack of control of cell proliferation. Especially in melanoma, this pathway has become a target for the development of oncogene-targeted therapies, such as the potent inhibitors of v-Raf murine sarcoma viral oncogene homolog B (BRAFi) and mitogen-activated protein kinase kinase (MEKi). Very high rates of response have been achieved, but most patients are relapsed due to the development of resistance, justifying the constant search for new therapeutic compounds. Early results from our group indicated that 4-nerolidylcatechol (4-NC), a catechol compound extracted from Pothomorphe umbellata, induces DNA damage, ROS production, increased p53 expression culminating in apoptosis in melanoma but with no data regarding the 4-NC effects in cells resistant to BRAFi or MEKi. Therefore, here we evaluated the role of 4-NC alone or in combination with BRAFi/MEKi in resistant melanoma cells. Double-resistant cells were generated and characterized by MAPK pathway reactivation. 4-NC alone or in combination (30 μM) with MAPK inhibitors was cytotoxic, inhibited colony formation and decreased invasiveness in two and three-dimensional cell culture models of treatment-naïve, BRAFi-resistant and BRAF/MEKi double-resistant melanoma cells. Apoptosis induction was demonstrated in resistant and double-resistant melanoma cell lines after 4-NC treatments. 4-NC showed important ability to induce apoptosis via Endoplasmatic Reticulum (ER) stress and specifically BiP and CHOP that had increased protein expression in all melanoma cell lines proving to be part of the ER stress pathway activation. CHOP knockdown slightly but enough increases cellular viability following 4-NC treatment indicating that apoptosis observed is partially dependent on CHOP. In summary, we show that 4-NC is a compound with activity against cutaneous melanoma, including resistant cells to clinically approved therapies.